1996
DOI: 10.1038/bjc.1996.218
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and risk of colorectal cancer in men and women

Abstract: Summary We examined the association between self-reported occupational and recreational physical activity and the subsequent risk of colorectal cancer in a population-based cohort in Norway. During a mean follow-up time of 16.3 years for males and 15.5 years for females, 236 and 99 colon cancers and 170 and 58 rectal cancers were observed in males and females, respectively, among 53 242 males and 28 274 females who attended the screening between 1972 and 1978. Physical activity at a level equivalent to walking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
139
3
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(157 citation statements)
references
References 34 publications
13
139
3
2
Order By: Relevance
“…Several cohort studies have shown that physical activity is negatively associated with colorectal cancer risk, and in accordance with our findings in men, a reduction of 40 to 50% has been reported (Wu et al, 1987;Lee et al, 1991;Giovannucci et al, 1995Giovannucci et al, , 1996Thune and Lund, 1996;Martinez et al, 1997). Two interpretations have been proposed for the reduced risk.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Several cohort studies have shown that physical activity is negatively associated with colorectal cancer risk, and in accordance with our findings in men, a reduction of 40 to 50% has been reported (Wu et al, 1987;Lee et al, 1991;Giovannucci et al, 1995Giovannucci et al, , 1996Thune and Lund, 1996;Martinez et al, 1997). Two interpretations have been proposed for the reduced risk.…”
Section: Discussionsupporting
confidence: 92%
“…Contrary to some other studies, we found no significant association with physical activity among women (Thune and Lund, 1996;Martinez et al, 1997). We also explored the effect of extreme levels of physical activity in women, but this did not change the results.…”
Section: Discussioncontrasting
confidence: 59%
“…Few cohort studies of physical activity and colon cancer have conducted analyses stratified by tumor sub-site [6,12,13,[16][17][18][32][33][34]36,37,48,49], with those that did yielding conflicting results. Some studies reported stronger inverse findings for the proximal colon [12,16,17,33,48], while others observed stronger inverse associations for distal colon sites [6,13,18,36,37]. Observed differences may be due to varying etiologies between tumors of the proximal and distal colon [50].…”
Section: Discussionmentioning
confidence: 99%
“…Results of the Fukuoka Colorectal Cancer Study showed that job-related as well as total and moderate leisure-time physical activity were associated with a significant reduction of rectal cancer risk in men only [51]. In contrast, several cohort studies [12,17,33] have failed to detect an association between physical activity and rectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies divided the physical activity into occupational and recreational (Thune and Lund, 1996;Marchand et al, 1997;Simons et al, 2013). Thune and Lund (1996) and Marchand et al (1997) documented that both occupational and recreational physical activities were inversely associated with colon cancer risk.…”
Section: Introductionmentioning
confidence: 99%